DIPLOMASI PERTAHANAN INDONESIA-UNI EMIRAT ARAB DALAM MEMBANGUN KEPERCAYAAN BERSAMA TAHUN 2014-2022 - Raka Gusfi; Arief Rachman; Lukman Yudho Prakoso (CV. AFDIFAL MAJU BERKAH, 2023)
This research paper explores the defense diplomacy efforts between Indonesia and the United Arab Emirates (UAE) through confidence-building measures (CBMs) as a strategic step to strengthen bilateral relations and increase trust between the two countries. The paper begins by discussing the historical context and the importance of defense diplomacy in the post-World War II era. It then examines the concept of defense strategy and its evolution beyond military operations. The role of diplomacy, particularly soft power diplomacy, is highlighted as an essential tool in international relations. The paper further delves into the concept of defense diplomacy, its peaceful use of armed forces, and its significance in addressing security challenges and building trust among countries. The focus is on the defense diplomacy efforts between Indonesia and the UAE and their impact on regional defense and security cooperation. The researchers employ a qualitative descriptive approach and a case study design to analyze the defense industry and defense cooperation efforts within the perspective of defense diplomacy. The results and discussions section presents an analysis of Indonesia's defense strategy, highlighting the objectives, means, and approaches employed in defense diplomacy with the UAE. The paper concludes by emphasizing the importance of defense diplomacy in enhancing bilateral relations, promoting regional stability, and leveraging the strengths and resources of both countries in the defense industry.